TEACHING ENGLISH PRONUNCATION BY USING “PROJECT BASED LEARNING (PBL)” METHOD IN ENGLISH CLASSES - Solnyshkina , Marina; G‘aybullayeva , Zilola (Scientific practical conference, 2025)
This study explores the teaching of English pronunciation in classes through the use of interactive methods, with a particular emphasis on applying Project-Based Learning (PBL) in group work. The research was organized into six main stages: preliminary preparation, planning, implementation, observation, reflection, and evaluation of results. Pronunciation, as a core component of English as a Foreign Language (EFL), is essential for developing effective oral communication. By improving their pronunciation, learners strengthen their ability to share ideas and opinions with clarity and confidence. Since pronunciation is a productive oral skill and the most common medium of verbal communication, its mastery is considered a crucial aspect of foreign language learning. The study highlights that PBL, as an interactive method, makes pronunciation lessons more engaging, effective, and meaningful in English classes.